2018
DOI: 10.1021/acs.energyfuels.8b00502
|View full text |Cite
|
Sign up to set email alerts
|

Removing Water from Diesel Fuel: Understanding the Impact of Droplet Size on Dynamic Interfacial Tension of Water-in-Fuel Emulsions

Abstract: Small amounts of water can enter diesel fuel during usage, causing major damage and failure of engine parts. Water is dispersed in fuel as droplets stabilized by the presence of surface-active compounds in the original fuel mixture as well as in fuel additives, including lubricity improvers and deposit control agents. Additives partition to the fuel–water interface and lower the interfacial tension (IFT), decreasing the ability to coalesce and separate water from fuel. The ability of standard coalescing filter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 67 publications
3
39
0
1
Order By: Relevance
“…Moreover, several studies have shown that surfactant transport to curved interfaces is governed not only by the surfactant concentration in the bulk phase but also by the curvature or radius of the interface . With water-in-diesel fuel emulsions, we previously showed that diffusion of surfactant to a highly curved, micrometer-sized droplet in flow is faster than that to a planar interface, resulting in the transport shifting toward being limited by kinetics rather than diffusion . These observations lead to the conclusion that coalescence behavior in emulsions, which contain micrometer-scale droplets, could be influenced not only by the surfactant concentration but also by the surfactant transport to and at the interface.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, several studies have shown that surfactant transport to curved interfaces is governed not only by the surfactant concentration in the bulk phase but also by the curvature or radius of the interface . With water-in-diesel fuel emulsions, we previously showed that diffusion of surfactant to a highly curved, micrometer-sized droplet in flow is faster than that to a planar interface, resulting in the transport shifting toward being limited by kinetics rather than diffusion . These observations lead to the conclusion that coalescence behavior in emulsions, which contain micrometer-scale droplets, could be influenced not only by the surfactant concentration but also by the surfactant transport to and at the interface.…”
Section: Introductionmentioning
confidence: 91%
“…29 With water-in-diesel fuel emulsions, we previously showed that diffusion of surfactant to a highly curved, micrometer-sized droplet in flow is faster than that to a planar interface, resulting in the transport shifting toward being limited by kinetics rather than diffusion. 30 These observations lead to the conclusion that coalescence behavior in emulsions, which contain micrometer-scale droplets, could be influenced not only by the surfactant concentration but also by the surfactant transport to and at the interface. Therefore, there is clearly a pressing need to conduct more controlled single-droplet coalescence experiments in the presence of surfactants on length and time scales relevant to real emulsions with microscale dispersed droplets.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Microfluidic methods, which require the use of a convective bulk flow, have also been developed to measure interfacial stress at micron-scale interfaces. Additional details on this technique can be found in references [164,165].…”
Section: Microscopic Dropsmentioning
confidence: 99%
“…Logo, um aditivo eficaz deve apresentar uma boa estabilidade térmica 54 e à oxidação 46,55 , apresentar alto potencial energético para favorecimento da queima nos motores, miscibilidade adequada com os combustíveis e em alguns casos, ser um agente contra microrganismos que possam proliferar nos tanques dos veículos 56 . Atividades adicionais podem estar contidas em alguns produtos, como por exemplo, poder detergente para limpeza de resíduos no sistema de combustível 57 e ação dispersante de água 58 . De forma geral, o custo adicional associado à utilização dos aditivos é inferior ao custo de reparos mecânicos devido à utilização de combustíveis de má qualidade que possam ter se deteriorado pela ausência de um aditivo adequado [59][60][61] .…”
Section: Aditivos Para Combustíveisunclassified